NFB-13. Rhabdoid Tumor Predisposition Syndrome (RTPS) – Finding Evidence by systematic Analyses. (3rd June 2022) - Nemes, Karolina; Bens, Susanne; Johann, Pascal D; Steinbügl, Mona; Gruhle, Miriam; Kachanov, Denis; Teleshova, Margarita; Hauser, Peter; Simon, Thorsten; Tippelt, Stephan; Eberl, Wolfgang; Woessmann, Wilhelm; et al.
Abstract: BACKGROUND: Individuals with rhabdoid tumor predisposition syndrome (RTPS1 – SMARCB1, RTPS2 – SMARCA4 ) have a propensity to develop malignant rhabdoid tumors (MRT). Affected patients typically present < age 12 months with synchronous tumors (SYN) exhibiting an unusually aggressive clinical behavior. Due to the rarity of RTPS, standards for management are evolving. METHODS: Clinical, genetic, and treatment data of 90 patients with RTPS from 16 countries were analyzed (2004 – 2020). Therapy followed the EU-RHAB recommendations. Tumors and matching blood samples were investigated for SMARCB1 and/or SMARCA4 mutations using FISH, MLPA and sequencing. DNA-methylation subgroups were determined using DNA methylation arrays. RESULTS: The median age at diagnosis of 52 girls and 38 boys was 5.5 months (0 – 203). 55.5% (50/90) of patients presented with an atypical teratoid/rhabdoid tumor (ATRT), 23.5% (21/90) demonstrated SYN, and 21% (19/90) extracranial MRT. RTPS1 was present in 84-, RTPS2 in six patients. In 77% (65/84) complete data on SMARCB1 mutational status were generated. Methylation subgroup status was available in 59% (40/68) of ATRT or SYN. The 5-year overall- (OS) and event free survival rates of patients with RTPS1 were 19.8 ± 4.8% and 15 ± 4.2%, respectively. Age < 1 year at diagnosis (10.1±4.3% vs. 46.7±11.1%), presence of SYN (5.3±5.1% vs. 24.8±6%), histological diagnosis (ATRT vs. eMRT/RTK/SYN) (26.8±7.1% vs. 11.9±5.6%), localized disease (34.5±8 vs. 8.3±4.6%), and presence of PGV at C-terminal (33±8.6% vs. 9.4±5.3%) were significant prognostic factors for 5-year OS in univariate analysis. INTERPRETATION: In the largest cohort of patients with RTPS, predictors significant for positive outcome could be detected: age > 1 year, absence of SYN, histological diagnosis ATRT, localized disease and PGV located at C-terminal. In our research project, we aim to characterize the complete pheno- and genotype of patients with RTPS to develop a risk score including surveillance recommendation.